Speeded up and low-powered hardware implementation of the secure hash algorithm through partial unrolling - Michail, Harris; Kakarountas, Athanasios P.; Theodoridis, Georgios A. (My University, 2005)
Applications that call for data integrity and signature authentication at electronic transactions invoke cryptographic primitives like hash functions. A hash function is utilized in the security layer of every communication protocol. However, as protocols evolve and new high-performance applications appear, the throughput of hash functions seems to reach to a limit. Market is asking for new implementations with higher throughputs respecting the tendency of the market to minimize devices' size and increase their autonomy to make them portable. The existing SHA-1 Hash Function implementations (SHA-1 is common in many protocols e.g. IPSec) limit throughput to a maximum of 2 Gbps. In this paper, a new a partially unrolled implementation is presented that comes to exceed this limit improving the throughput by 53%. Power issues have also been taken in consideration, in such way that the proposed implementation can be characterized as low-power.
Keywords: Algorithms; Electronic commerce; Data integrity; Hardware